Fermi-Walker Derivation of Magnetic Curves According to The Alternative Frame - Yeneroglu, Mustafa; Tan, Ahmet (My University, 2025)
Many studies have been carried out according to different frame In the theory of curves in Euclidean space. The alternative frame is a this frame. In this paper, we investigate the Ferimi-Walker derivative of magnetic curves according to the alternative frame. Firstly, we analysed the magnetic curves in the alternative frame We defined N-magnetic, C-magnetic and W-magnetic curves. Then, the Fermi-Walker derivation and theorems in this frame are examined for N-magnetic, C-magnetic and W-magnetic curves.
Keywords: Alternative frame; magnetic curves; Fermi-Walker derivations